Single-cell insights into the hematopoietic generation of T lymphocyte precursors in mouse and man - Rothenberg, Ellen V. (Exp Hematol, 2021)
T cell development is a major branch of lymphoid development and a key output of hematopoiesis, especially in early life, but the molecular requirements for T-cell potential have remained obscure. Considerable advances have now been made toward solving this problem through single-cell transcriptome studies, interfaced with in vitro differentiation assays that monitor potential efficiently at the single cell level. This review focuses on a series of recent reports studying mouse and human early T cell precursors, both in the developing fetus and in stringently purified postnatal samples of intrathymic and prethymic T-lineage precursors. Cross-comparison of results shows a robustly conserved core program in mouse and human, but with some informative and provocative variations between species and between ontogenic states. Repeated findings are the multipotent progenitor regulatory signature of thymus-seeding cells and the proximity of the T cell program to dendritic cell programs, especially to plasmacytoid dendritic cells in humans.